Soil slope stability in road construction on soft ground - Abdul Jamil, Nor Suhana (2020)
Slope stability assessment is a fundamental step in evaluating the safe design of structures and infrastructures especially for road construction. This is very crucial to ensure the slope can effectively function to protect earth soil from landslide and in addition, to allow for vehicle passing through the road safely. In the routine of geotechnical analysis, the use of limit equilibrium (LE) methods with a Mohr- Coulomb are criterion is the preferred option to examine the factor of safety for slopes. This is usually done by using a 2D approximation that corresponds as closely as possible to the good credible scenario. Various commercial software up to date can be used today for the purpose and in this study, SLOPE/W software is used to analyse the slope stability. In addition, analytical analysis also carried out via elastic and consolidation analysis to obtain the settlement condition. In this study, a selected case study of a new proposed road construction approximately 5.0 km in length is located between the state road route of M131, (Hutan Percha Gemencheh) and state road route of M19, (Tebong Ayer Pasir), Alor Gajah, Melaka) is presented. A parametric analyses of different height of embankment is carried out to investigate the outcome of factor of safety (FOS) and settlement. Results show that for the selected critical case study area, the slope model with height proposed embankment of height of 14 m lead to factor of safety less than 1.3 with certain value of settlement.